Whisker and Nose Tactile Sense Guide Rat Behavior in a Skilled Reaching Task - Parmiani, Pierantonio; Lucchetti, Cristina; Franchi, Gianfranco (Frontiers in Behavioral Neuroscience, 2018)
Skilled reaching is a complex movement in which a forelimb is extended to grasp food for eating. Video-recordings analysis of control rats enables us to distinguish several components of skilled reaching: Orient, approaching the front wall of the reaching box and poking the nose into the slot to locate the food pellet; Transport, advancing the forelimb through the slot to reach-grasp the pellet; and Withdrawal of the grasped food to eat. Although food location and skilled reaching is guided by olfaction, the importance of whisker/nose tactile sense in rats suggests that this too could play a role in reaching behaviour. To test this hypothesis, we studied skilled reaching in rats trained in a single-pellet reaching task before and after bilateral whisker trimming and bilateral infraorbital nerve (ION) severing. During the task, bilaterally trimmed rats showed impaired Orient with respect to controls. Specifically, they detected the presence of the wall by hitting it with their nose (rather than their whiskers), and then located the slot through repetitive nose touches. The number of nose touches preceding poking was significantly higher in comparison to controls. On the other hand, macrovibrissae trimming resulted in no change in reaching/grasping or withdrawal components of skilled reaching. Bilaterally ION-severed rats, displayed a marked change in the structure of their skilled reaching. With respect to controls, in ION-severed rats: a) approaches to the front wall were significantly reduced at 3–5 and 6–8 days; b) nose pokes were significantly reduced at 3–5 days, and the slot was only located after many repetitive nose touches; c) the reaching-grasping-retracting movement never appeared at 3–5 days; d) explorative paw movements, equal to zero in controls, reached significance at 9–11 days; e) the restored reaching-grasping-retracting sequence was globally slower than in controls, but the success rate was the same. These findings strongly indicate that whisker trimming affected Orient, but not the reaching-grasping movement, while ION severing impaired both Orient (persistently) and reaching-grasping-retracting (transiently, for 1–2 weeks) components of skilled reaching in rats.